Imaginários e saberes docentes na escola inclusiva: um estudo dos processos de formação e autoformação - Dal-Forno, Josiane Pozzatti (2005)
This work is inserted in the line of teachers education and presents the research carried out with three elementary school teachers who work with students with special needs. They are included in the regular classroom in a public school from Santa Maria, RS. The inclusion became a challenge mainly for teachers that are not graduated in Special Education. In this way, one searched an approximation in the representation of these teachers in relation to the school inclusion by aiming to understand the construction of teachers knowledge in this context. The social imaginary served as theoretical support by making possible to know instituted images and images which institute in the teachers representations. The used methodology was based on memory, an essential instrument in the work with Life History because it promotes the resumption of experiences during the education journey. With this investigation, one noted that, although the collaborator teachers do not have professional knowledge concerning the deficiencies, they construct experienced knowledge before the needs that arise daily. It means that teachers learn to work with the included students in the everyday professional practice and experience. Besides that, one perceived the influence of another two factors over the learning of those teachers facing the inclusion: interaction with colleagues and time. The interaction they establish with colleagues and mainly with the special educators from the school is fundamental in order to change information and knowledge aiming as well as to elaborate teaching strategies. Teachers knowledge is a temporal construction and teaching supposes learning and dominating progressively the knowledge to work. To work with included students is also a construction crossed by temporality and learning. Besides, one noted that school could be thought as a space/time of education involving everyone in the inclusion process.